Penggunaan Teknologi Informasi Dan Komunikasi (TIK) Dalam Pelayanan Publik - Hidayat, Dayat (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
It is a government compulsary to enhance better services for their citizens. Many rules and efforts are created to make these services more convenient. The use of a informations and technology is one of the efforts to make the services closser to the citizens, it called e-government.